Optimal Timing and Treatment Modalities of Arytenoid Dislocation and Subluxation: A Meta-Analysis - Frosolini, Andrea; Caragli, Valeria; Badin, Giulio; Franz, Leonardo; Bartolotta, Patrizia; Lovato, Andrea; Vedovelli, Luca; Genovese, Elisabetta; de Filippis, Cosimo; Marioni, Gino (Medicina (Kaunas, Lithuania), 2025)
Background and Objective: Arytenoid dislocation (AD) and subluxation (AS) impact vocal fold mobility, potentially affecting the quality of life. Their management, including the timing and modality of treatment, remains a subject of research. Our primary objective was to assess and compare the available treatment strategies for AS and AD. Material and methods: the protocol was registered on PROSPERO (CRD42023407521). Manuscripts retrieved from a previously published systematic review were evaluated. To comprehensively cover the last 25 years, an updated literature search was conducted, screening PubMed, Scopus, and Cochrane databases. Review Methods: We included studies that reported treatment modalities and the time to treatment (TT) for AS/AD, with outcomes objectively evaluated. Data on treatment success were pooled, and the impact of TT on recovery outcomes was analyzed. Results: Thirteen studies involving 361 patients were included. The majority of cases were attributed to iatrogenic trauma following intubation. Closed reduction (CR) was the primary treatment, with high success rates for both general (success rate: 77%, CI: 62–87%) and local anesthesia (success rate: 89%, CI: 70–97%). The standardized mean difference for the TT effect on treatment outcome was −1.24 (CI: −2.20 to −0.29). Conclusions: The absence of randomized controlled trials and the overall moderate-to-low quality of the studies highlighted the importance of the finding’s careful interpretation. This meta-analysis underscores the effectiveness of CR in managing AS/AD, with both general and local anesthesia yielding high success rates. The findings highlight the importance of TT, suggesting that early intervention is paramount. Future clinical research is needed to further refine these findings and optimize treatment protocols.